The Tubingen School - HARRIS, Horton; ELLIS, E Earle (forword) (Grand Rapids Baker, 1990)
new
School of F C Baur
Keywords: HISTORY - 19TH CENTURY; NEW TESTAMENT - CRITICISM, INTERPRETATION, ETC; PROTESTANT - THEOLOGY